Rational testing for gene fusion in colorectal cancer: MSI and RAS-BRAF wild-type metastatic colorectal cancer as target population for systematic screening. (July 2022) - Delaye, Matthieu; Ibadioune, Sabrina; Julié, Catherine; Marin, Cristi; Peschaud, Frédérique; Lupinacci, Renato; Vacher, Sophie; Ahmanache, Ladidi; Antonio, Samantha; Schnitzler, Anne; Buecher, Bruno; Mariani, Pascale; et al.
Abstract: Gene fusions provide access to new therapeutic opportunities for patients treated for a colorectal cancer (CRC). However, they do not excess 1% of patients. A better identification of patients in whom gene fusions are highly prevalent is a major issue in a therapeutic and medico-economics perspective. This study assesses the rates of gene fusions in CRC patients with MSI/ RAS-BRAF WT in our routine practice detected with a commercially available NGS-based fusion panel. Among the 130 MSI CRC tumors, 43 (33%) were KRAS-NRAS-BRAF WT . A gene fusion was detected in 7 (25.9%) of the 27 MSI/ RAS-BRAF WT samples, which had RNA suitable for analysis after quality control. These fusions involved mainly NTRK1/3 (n = 5), as well as ALK (n = 1) and BRAF (n = 1). In the present study, we confirm that patients with MSI/RAS-BRAF WT CRCs represent a subpopulation in which targetable gene fusions are overrepresented. Our results support the use of a two-step algorithm for molecular screening, in which metastatic CRC patients would have routine MSI and RAS/BRAF testing, and then only those with MSI/RAS-BRAFWT would be screened with dedicated NGS RNA panel for gene fusions. Highlights: Gene fusions do not excess 1% of patients with colorectal cancer (CRC). Gene fusions are overrepresented in patients with MSI/RAS-BRAF WT CRC. Most of gene fusions provide access to new therapeutic opportunities. Our results support the use of a two-step algorithm for molecular screening.